Homecoming queers : desire and difference in Chicana Latina cultural production - Danielson, Marivel T. (New Brunswick, N.J. : Rutgers University Press, 2009)
Homecoming Queers provides a critical discussion of the multiple strategies used by queer Latina authors and artists in the United States to challenge silence and invisibility within mainstream media, literary canons, and theater spaces. Marivel T. Danielson's analysis reveals the extensive legacy of these cultural artists, including novelists, filmmakers, students and activists, comedians, performers, and playwrights. By clearly discussing the complexities and universalities of ethnic, racial, sexual, gender, and class intersections between queer Chicana and U.S. Latinas, Danielson ex.
Queering home: desire meets theory meets art -- Speaking selves: language and identity in transition -- Moving violations: performing the limits of representation in Marga Gomez's Jaywalker -- The birdy and the bees: queer Chicana girlhood in Carla Trujillo's What night brings -- Complicating community: Terri De La Peña, Cristina Serna, Frances Negrón Muntaner, Ela Troyano, and Carmelita Tropicana -- The erotics of home: Monica Palacios, Marga Gomez, and Carmelita Tropicana -- Dancing with devils: gendered violence in novels by Emma Pérez and Achy Obejas -- Our art is our weapon: women of color transforming academia.
Includes bibliographical references (pages 201-209) and index.
Print version record.
JSTOR
Keywords: American literature -- Hispanic American authors -- History and criticism; American literature -- Women authors -- History and criticism; Lesbians' writings, American -- History and criticism; Home in literature; Hispanic Americans in the performing arts; Hispanic American lesbians -- Intellectual life; Space in literature; Languages & Literatures; American Literature; English; Littérature américaine -- Auteurs américains d'origine latino-américaine -- Histoire et critique; Écrits de femmes américains -- Histoire et critique; Écrits de lesbiennes américains -- Histoire et critique; Foyer dans la littérature.; Américains d'origine latino-américaine dans les arts du spectacle; Lesbiennes américaines d'origine latino-américaine -- Vie intellectuelle; Espace dans la littérature.; ART -- Reference; ART -- Performance; SOCIAL SCIENCE -- Gay Studies; Lesbianismo -- En la literatura; Literatura hispanoamericana -- Autoras -- Historia y crítica; American literature -- Hispanic American authors; American literature -- Women authors; Hispanic Americans in the performing arts; Home in literature; Lesbians' writings, American; Space in literature; Lesbe; Autorin; American Literature; English; Languages & Literatures; Littérature américaine -- Auteurs d'origine latino-américaine -- Histoire et critique; Littérature hispano-américaine -- Femmes écrivains -- Thèmes, motifs; Écrits de lesbiennes américaines -- Thèmes, motifs; Foyer -- Dans la littérature.; Américains d'origine latino-américaine -- Et les arts du spectacle; Hispanos; Criticism, interpretation, etc